STATIC ANALYSIS OF NARA 4308 LATHE MACHINE STRUCTURE - Beriti Sinurat, Natan
Machine tools are machines used in the production process to make an item or object with precise and accurate results. In this research, the machine tool that is the object of research is a lathe. Therefore, to get precise and accurate workpieces produced by the lathe, the lathe must be rigid. The stiffness of the lathe is obtained from the distribution of deformations produced by the load on the lathe. This research was carried out on self-loading and loading caused by the addition of work objects. Deformation analysis is carried out by determining a reference point for data collection, this point is called a remote point. The deflection produced by the loading will be analyzed in this research to analyze the stiffness of the lathe. The simulation results and analysis of load variations show that the maximum deformation on the lathe is -10.655 microns while the minimum value is -7.1728 microns. The NARA 4308 lathe has a feature, named tension bar, this feature is used to maintain the structure of the NARA 4308 lathe. This research involves the tension bar as one of the variables in the simulation process by iterating the force that will be provided by the tension bar. Iterations on the tension bar force showed that the optimal value for the tension bar force was 2100 N. The simulation results were involved in simulating load variations so that the maximum deformation was -8.4732 microns and the minimum value was -5.2732 microns. The analysis and simulation show that there is an influence of the tension bar tension on the lathe to maintain the geometry of the structure.